Finite Difference Method for Solving Material Balance Equation in Lithium-Ion Cell - Y, Norzihani (2010)

(untitled)
The objective of this paper is to present the solution to the material balance equation in the solution phase for separator and cathode. A simplified model is used to describe the discharge of rechargeable lithium batteries. During the discharge process the lithium-ion de-intercalate from the anode (electrode negative), diffuse through the separator and intercalate into the cathode (electrode positive). Many works have been done such as the thermal analysis, energy balance analysis and charge/discharge analysis. However, the solutions in this paper only focus on the concentration profile during the discharge process of lithium-ion under galvanostatic discharge in the separator and the cathode.